Oxidative Dehydrogenation of Propane in the Realm of Metal–Organic Frameworks - Korzyński, Maciej Damian; Dincă, Mircea (ACS central science, 2017)
Metal−organic framework-based catalytic formation of propene holds promise for low temperature sustainable production of this important feedstock.